FAKTOR RISIKO STUNTING DARI PERSPEKTIF PROMOSI KESEHATAN IBU BALITA - Ajeng Athalia; Safrudin Safrudin; Wahyudin Rajab (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2025)
Stunting is a chronic nutritional problem that has long-term impacts on children’s physical growth and cognitive development. In Kelurahan Galur, Central Jakarta, stunting remains one of the top ten priority health issues, indicating that its prevention requires not only medical approaches but also health promotion strategies emphasizing community empowerment and behavior change. This study aimed to analyze the factors associated with stunting among children under five, focusing on maternal knowledge, maternal attitudes toward parenting, environmental sanitation, family support, and the role of health workers. A quantitative method with a cross-sectional design and proportional random sampling technique was employed, while data were collected using questionnaires and analyzed through chi-square tests. The results showed significant associations between maternal knowledge, maternal attitudes, environmental sanitation, and family support with the risk of stunting, whereas the role of health workers did not demonstrate a significant relationship. These findings highlight that health promotion–related factors play a crucial role in preventing stunting. Therefore, interventions directed at improving maternal knowledge, changing maternal attitudes, enhancing environmental sanitation, strengthening family support, and optimizing the role of health workers are essential to reduce the prevalence of stunting in Kelurahan Galur.